2017
DOI: 10.2174/1871529x16666161130123937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Outpatient Service Rehabilitation Programme in Patients Affected by Pulmonary Arterial Hypertension: An Observational Study

Abstract: Cardiorespiratory training in a outpatient service is a suitable option for patients with PAH in WHO FC II/III thanks to improved exercise capacity and QoL, which may allow them to achieve better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 33 publications
1
53
0
1
Order By: Relevance
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Data for 519 patients are available for exercise training at ∼60% of peak heart rate, not exceeding 120 beats•min −1 , with an oxygen saturation greater than 85-90% [68]. Additional respiratory training was performed in the inpatient studies in Germany, one outpatient based study in Italy [36] and one home-based study in Japan [32]. This training component was aimed at strengthening the respiratory muscles and to increase the awareness of different breathing patterns and techniques [69].…”
Section: Training Components and Intensitymentioning
confidence: 99%
“…nCPET may be useful diagnostically, however, only when targeted to specific at-risk populations such as scleroderma patients 32 or those in whom PH is suspected by echocardiograpy. 33 Data from nCPET incrementally predicts mortality when added to resting hemodynamics. 20 However, using baseline data, nCPET adds marginal value when added to the prognostic capabilities of the 6MWD, 34 but nCPET may add incremental prognostic value in clinically stable patients on therapy.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 While elevated V E/V CO 2 relationships may be explained by reduced lung perfusion and an increase of dead space ventilation in the affected areas, hypocapnia demonstrates that there is an additional component of hyperventilation present and visible already at rest. 33 Recent studies have shown that autonomic nervous system disturbances may play an important role in ventilatory inefficiency, and that there may be an additional component of increased chemoreceptor sensitivity leading to hyperventilation in PAH. 34 Farina et al 35 demonstrated that ventilatory responses to brief periods of inspiratory hypoxia and steady-state hyperoxic hypercapnia in subjects with PAH were about twofold greater than in matched controls.…”
Section: The Pulmonary Ventilation/perfusion Relationshipmentioning
confidence: 99%
“…Verma et al [273] suggest a combination of pharmacotherapy and psychotherapy, in particular CBT. There exist few studies on psychological interventions in pulmonary hypertension [275][276][277]. In particular, attention is focused on the teaching of relaxation and slow breathing techniques [275,277].…”
Section: Psychological Interventionsmentioning
confidence: 99%